Inhibition of Aspirin-Induced Gastrointestinal Injury: Systematic Review and Network Meta-Analysis - Zhang, Wan-tong; Wang, Miao-ran; Hua, Guo-dong; Li, Qiu-yan; Wang, Xu-jie; Lang, Rui; Weng, Wei-liang; Xue, Chun-miao; Zhu, Bao-chen (Frontiers in Pharmacology, 2021)
Background: Administration of aspirin has the potential for significant side effects of gastrointestinal (GI) injury mainly caused by gastric acid stimulation, especially in long-term users or users with origin gastrointestinal diseases. The debate on the optimal treatment of aspirin-induced gastrointestinal injury is ongoing. We aimed to compare and rank the different treatments for aspirin-induced gastrointestinal injury based on current evidence. Methods: We searched MEDLINE, Embase, Web of Science, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and Chinese databases for published and unpublished randomized controlled trials (RCTs) of different treatments for aspirin-induced gastrointestinal injury from inception to 1 May 2021. All of the direct and indirect evidence included was rated by Network metaanalysis under a Bayesian framework. Results: A total of 10 RCTs, which comprised 503 participants, were included in the analysis. The overall quality of evidence was rated as moderate to high. Eleven different treatments, including omeprazole, lansoprazole, rabeprazole, famotidine, geranylgeranylacetone, misoprostol, ranitidine bismuth citrate, chili, phosphatidylcholine complex, omeprazole plus rebamipide and placebo were evaluated in terms of both efficacy and acceptability. According to these two dimensions, it was suggested that omeprazole plus rebamipide outperformed other treatments, whereas geranylgeranylacetone and placebo were among the least treatment. Conclusion: This is the first systematic review and network meta-analysis of different treatments for aspirin-induced gastrointestinal injury. Our study suggested that omeprazole plus rebamipide might be considered the best option to treat aspirin-induced gastrointestinal injury. More multicenter, high quality, large sample size randomized controlled trials will confirm the advantages of these medicine in the treatment of aspirin-induced gastrointestinal injury in the future.